Ketimpangan Antardaerah, Desentralisasi dan Eksistensi Korupsi di Indonesia - Sukadana, I Wayan (UI Scholars Hub, 2009)
Decentralization has been implemented for eight years. However, corruption has not been lessened yet within the decentralization era. Bad regulations and investment climate are suspected to be a cause of the situations. Good regulation and investment climate appear if the interjurisdictional competitions exist. The incentive for competition is the equality of economic endowment among regions, or each region has their own tradeable